GDP and the value of family caretaking: How much does Europe care? - Gianna Claudia Giannelli; Lucia Mangiavacchi; Luca Piccoli (Institute for the Study of Labor (IZA), 2010)
This study estimates the size and value of unpaid family caretaking activities at a European level. While at a country level several studies are available, a comprehensive evaluation for Europe as a whole was missing so far, mainly due to data limitations. This paper fills this gap using a method that merges the information of an EU household survey (EU-SILC) with a time use survey (HETUS). Monetary values of unpaid family domestic work and unpaid family childcare work are obtained applying both the opportunity cost and the market replacement approaches. For Europe as a whole, the total value of these activities ranges between 20.1 per cent and 36.8 per cent of the EU GDP, depending on the applied methodology. The national values of these activities are discussed and an interpretation of the country differentials in the family caretaking gender gaps is given in terms of differences in culture, economic development and welfare state.
Keywords: D19; J16; R20; 330; Unpaid domestic work; family care work; gender inequality; opportunity cost; market replacement approach; Kinderbetreuung; Hausarbeit; Zeitbudgetforschung; Opportunitätskosten; Sozialprodukt; Geschlecht; Schätzung; Institutionalismus; EU-Staaten